Impulse oscillometry and obesity in children - Maíra S. de Assumpção; José D. Ribeiro; Renata M.G. Wamosy; Fernanda C.X.S. de Figueiredo; Paloma L.F. Parazzi; Camila I.S. Schivinski (Elsevier, 2018)
Objective: To compare impulse oscillometry system parameters of normal-weight children with overweight and obese children. Method: All participants were submitted to the evaluation of lung function (spirometry and impulse oscillometry) following the American Thoracic Society standards. The evaluation of respiratory mechanics was performed using the Jaeger™ MasterScreen™ Impulse Oscillometry System (Erich Jaeger, Germany), three tests were recorded, with acquisition for at least 20 seconds. Results: The study included 81 children (30 in the control group, 21 in the overweight group, and 30 the in obesity group), matched for age and sex. Regarding spirometry data, obesity group showed higher numerical values in relation to the control group; however, there were no significant differences among the three groups. For impulse oscillometry parameters, there was a difference between control group and obesity group for respiratory impedance (p = 0.036), resistance at 5 hertz (p = 0.026), resonant frequency (p = 0.029), and reactance area (p = 0.014). For the parameters expressed in percentage of predicted, there were differences in resistance at 5 hertz, resonant frequency, and reactance area between control group and obesity group. Conclusions: Obese children showed increased oscillometry parameters values representative of airway obstruction, compared to normal-weight children. Changes in some oscillometry parameters can already be observed in overweight school-aged children. Resumo: Objetivo: Comparar parâmetros do Sistema de Oscilometria de Impulso de crianças com peso normal com crianças com sobrepeso e obesas. Método: Todos os participantes foram submetidos à avaliação de mecanismos respiratórios utilizando o Sistema de Oscilometria de Impulso Jaeger™ (MasterScreen™ IOS,Erich Jaeger, Alemanha) seguindo as normas da Sociedade Torácica Americana. Todos os participantes foram submetidos a testes de espirometria e oscilometria (três testes foram registrados, com coleta de dados por pelo menos 20 segundos). Resultados: O estudo incluiu 81 crianças (30 no grupo de controle, 21 no grupo sobrepeso e 30 no grupo obesidade), pareadas por idade e sexo. No que diz respeito a dados de espirometria, o grupo obesidade mostrou valores numéricos mais elevados; contudo, não houve diferenças significativas entre os três grupos. No que diz respeito a parâmetros do Sistema de Oscilometria de Impulso, houve diferença entre o grupo de controle e o grupo obesidade em Z5 (p = 0,036), resistência 5 hertz (p = 0,026), frequência de ressonância (p = 0,029) e área de reatância (p = 0,014). Nos parâmetros expressos em percentual previsto, houve diferenças em resistência 5 hertz, frequência de ressonância e área de reatância entre o grupo de controle e grupo obesidade. Conclusões: Crianças obesas mostraram parâmetros de oscilometria aumentados representativos de obstrução das vias aéreas em comparação a crianças com peso normal. As alterações em alguns parâmetros oscilométricos já podem ser observadas em crianças com sobrepeso em idade escolar. Keywords: Children, Obesity, Oscillometry, Palavras-chave: Crianças, Obesidade, Oscilometria